Evolution history dominantly regulates fine root lifespan in tree species across the world - Xingzhao Huang; Zhouying Lu; Fangbing Li; Yang Deng; Fangfang Wan; Quancheng Wang; Fousseni Folega; Jinsong Wang; Zijian Guo (Forest Ecosystems)
Understanding the drivers of variations in fine root lifespan is key to informing nutrient cycling and productivity in terrestrial ecosystems. However, the general patterns and determinants of forest fine root lifespan at the global scale are still limited. We compiled a dataset of 421 fine root lifespan observations from 76 tree species globally to assess phylogenetic signals among species, explored relationships between fine root lifespan and biotic and abiotic factors, and quantified the relative importance of phylogeny, root system structure and functions, climatic and edaphic factors in driving global fine root lifespan variations. Overall, fine root lifespan showed a clear phylogenetic signal, with gymnosperms having a longer fine root lifespan than angiosperms. Fine root lifespan was longer for evergreens than deciduous trees. Ectomycorrhizal (ECM) plants had an extended fine root lifespan than arbuscular mycorrhizal (AM) plants. Among different climatic zones, fine root lifespan was the longest in the boreal zone, while it did not vary between the temperate and tropical zone. Fine root lifespan increased with soil depth and root order. Furthermore, the analysis of relative importance indicated that phylogeny was the strongest driver influencing the variation in forest fine root lifespan, followed by soil clay content, root order, mean annual temperature, and soil depth, while other environmental factors and root traits exerted weaker effects. Our results suggest that the global pattern of fine root lifespan in forests is shaped by the interplay of phylogeny, root traits and environmental factors. These findings necessitate accurate representations of tree evolutionary history in earth system models to predict fine root longevity and its responses to global changes.